2015
DOI: 10.1063/1.4918672
|View full text |Cite
|
Sign up to set email alerts
|

Response analysis of a laminar premixed M-flame to flow perturbations using a linearized compressible Navier-Stokes solver

Abstract: International audienceThe response of a laminar premixed methane-air flame subjected to flow perturbations around a steady state is examined experimentally and using a linearized compressible Navier-Stokes solver with a one-step chemistry mechanism to describe combustion. The unperturbed flame takes an M-shape stabilized both by a central bluff body and by the external rim of a cylindrical nozzle. This base flow is computed by a nonlinear direct simulation of the steady reacting flow, and the flame topology is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
4
18
1
Order By: Relevance
“…With our choice of chemical parameters we reach a flame speed of S d = 2.9ms −1 and a flame width of 0.007mm, which amounts to about 1% of the inlet-tube outer radius. Despite a discrepancy between parameters and values typically observed in real configurations, Blanchard et al (2015) showed that -for parameter values similar to ours -transfer functions could Table 3: Parameter values used in our study.…”
Section: Optimal Gainscontrasting
confidence: 43%
See 2 more Smart Citations
“…With our choice of chemical parameters we reach a flame speed of S d = 2.9ms −1 and a flame width of 0.007mm, which amounts to about 1% of the inlet-tube outer radius. Despite a discrepancy between parameters and values typically observed in real configurations, Blanchard et al (2015) showed that -for parameter values similar to ours -transfer functions could Table 3: Parameter values used in our study.…”
Section: Optimal Gainscontrasting
confidence: 43%
“…To achieve this we use the values shown in table 3. The most prominent compromise that had to be made is the low Reynolds number and the large Mach number compared to experimental values (Blanchard et al 2015), yielding a large velocity upstream of the combustion zone of 35ms −1 and a small outer radius of the inlet at 0.64mm. With our choice of chemical parameters we reach a flame speed of S d = 2.9ms −1 and a flame width of 0.007mm, which amounts to about 1% of the inlet-tube outer radius.…”
Section: Optimal Gainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flames submitted to a non-zero tangential velocity tend to propagate wrinkles along the flame front, as sketched in figure 1; this is true even for stable flame configurations (Blackshear 1953;Petersen & Emmons 1961;Boyer & Quinard 1990). This well-known behaviour was recently analysed within a linear framework (Blanchard et al 2015). Flame perturbations then appear as a superposition of (1) entropy and reaction waves, associated with flame-front displacement, and (2) vorticity waves that enforce mass conservation across the dilatation zone; at the flame tip, this set of waves becomes unstable before it disappears.…”
Section: Configuration Modelling Approach and Numerical Detailsmentioning
confidence: 90%
“…A chemistry model of this type has been used by Williams (1985) to analytically study planar flame fronts. Details about the numerical discretization of our governing equations can be found in Sandberg (2007) and Blanchard et al (2015). Our simulations use a conservative formulation of the state variable q = (ρ, ρu r , ρu θ , ρE, ρY f ) T with ρ as the density, (u r , u θ ) as the radial and angular velocity, respectively, E as the total energy and Y f as the fuel mass fraction.…”
Section: Configuration Modelling Approach and Numerical Detailsmentioning
confidence: 99%